Investing to kill: return on investment of tobacco companies compared to high-mortality and neutral industries. Issue 1 (31st December 2022) - Hollman, Madeleine R.; Pearce, Joshua M.
ABSTRACT: Terrorists have worked directly with tobacco companies and used tobacco sales to fund traditional terrorist activities. This familiarity with tobacco, coupled with the high mortality rate of tobacco indicates terrorists may use tobacco investing as a means of covert legal killings (CLK), which refers to the terrorist intention of mass killing in a targeted group using legal means. To provide insight into tobacco investors' motives this study 1) quantifies annual death rate for leading mortality-causing industries in America.; 2) identifies eight companies responsible for the highest CLK; 3) compares investment returns for eight high-mortality companies to the S&P 500 from 2009 to 2019 to determine if tobacco is the most likely target for terrorist-based CLK. The top three highest mortality rate companies and thus best CLK investments from a terrorist perspective were tobacco companies: Altria Group Inc., Reynolds America Inc., and Imperial Brands. Together, these tobacco companies are responsible for >436, 800 American premature deaths/year, yet tobacco investments performed worse than the S&P500 over the last decade. It is clear that for CLK investors, tobacco is the most efficient means of investing to kill Americans. Questionable tobacco investor intentionality, combined with the recent advancement in CLK theory makes it reasonable to assume that some tobacco investors are terrorists using their wealth to specifically target and kill Americans. To determine how widespread this practice is, future work is needed to evaluate CLK tobacco investors against the Terrorist Screening Database.